2013
DOI: 10.3109/14767058.2013.818970
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum complications with cesarean delivery: a review of Maternal-Fetal Medicine Units Network publications

Abstract: Our analysis provides an overview of peripartum M/M with CD; it allows clinicians to counsel women who had or are having CD. It also permits study design, with an appropriate sample size, with the aim to minimize the morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(52 citation statements)
references
References 67 publications
0
52
0
Order By: Relevance
“…[9][10][11][12][13][14] Transfusion is an important component of counseling women in decision-making around their next birth after cesarean. 15 Most studies report actual birth method rather than intent, which makes counseling women near term difficult. 13 One review of published VBAC literature found rates of transfusion and hemorrhage did not significantly differ for women who had a trial of vaginal birth compared with an ERCS at the birth after cesarean.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Transfusion is an important component of counseling women in decision-making around their next birth after cesarean. 15 Most studies report actual birth method rather than intent, which makes counseling women near term difficult. 13 One review of published VBAC literature found rates of transfusion and hemorrhage did not significantly differ for women who had a trial of vaginal birth compared with an ERCS at the birth after cesarean.…”
Section: Introductionmentioning
confidence: 99%
“…Any increase in the risk of blood transfusion that results directly from interventions that decrease the NTSV cesarean delivery rate should be considered in the context of the risks and benefits of vaginal delivery compared to primary cesarean delivery; the risk of transfusion with primary cesarean delivery is approximately 2%–4%. 2 …”
Section: Discussionmentioning
confidence: 99%
“…There is an increased risk of hemorrhage, deep vein thrombosis, infection, complications from anesthesia, complications with future pregnancies (uterine rupture and morbidly adherent placenta), and neonatal respiratory problems with cesarean delivery compared to vaginal delivery. 2 Cesarean delivery also is associated with a longer hospital stay and increased cost. 3 Primary cesarean deliveries account for more than half of all cesarean deliveries, and the most common indication for repeat cesarean delivery is previous cesarean delivery.…”
mentioning
confidence: 99%
“…Operative vaginal births are associated with higher rates of both maternal and fetal trauma as well as postpartum hemorrhage [3034]. Cesarean deliveries are associated with a higher rate of hemorrhage, endometritis, venous thromboembolism and longer recovery [35]. These complications happen with greater frequency during emergency cesarean sections [35].…”
Section: Discussionmentioning
confidence: 99%
“…Cesarean deliveries are associated with a higher rate of hemorrhage, endometritis, venous thromboembolism and longer recovery [35]. These complications happen with greater frequency during emergency cesarean sections [35]. In future pregnancies, a primary cesarean section is also associated with higher rates of abnormal placentation, and uterine rupture [36] and is the major indication for a further cesarean section [3740].…”
Section: Discussionmentioning
confidence: 99%